PERAN KOMUNIKASI KELUARGA DALAM PEMBENTUKAN IDENTITAS REMAJA AKHIR DI KALANGAN MAHASISWA AKADEMI KOMUNIKASI RADYA BINATAMA - Dwi Nurrahmi Kusumastuti (Jurnal Ilmu Komunikasi AKRAB, 2023)
Teenage identity is a complex process involving the exploration of values,interests, social roles, and self-perceptions. One of the factors influencing this identitydevelopment is the family environment. The family is the first environment in whichteenagers interact and shape their thought patterns and behaviors. This study aims toanalyze the role of family communication in the process of forming late adolescent identityamong students of Radya Binatama Communication Academy, aged 18-21 years. Theresearch method used is Quantitative with a descriptive approach. Based on the resultsand discussions, it can be concluded that communication intensity within the family isprimarily carried out, especially with mothers, fathers, and siblings living together. Formsof care from parents and siblings are strongly perceived by students as a form of support.Harmony within family relationships still exists, enabling continued family gatherings thatfoster open communication with both parents and siblings, as well as social life outsidethe home. In the study on the role of family communication in the formation of lateadolescent identity among students of Radya Binatama Communication Academy, it canbe concluded that family communication significantly influences the development andformation of teenage identity.Keywords: Family Communication, Teenage Identity, Communication Intensity